Divergent effects of α- and β-myosin heavy chain isoforms on the N terminus of rat cardiac troponin T - Mamidi, Ranganath (The Rockefeller University Press, 2013)
Divergent effects of α– and β–myosin heavy chain (MHC) isoforms on contractile behavior arise mainly because of their impact on thin filament cooperativity. The N terminus of cardiac troponin T (cTnT) also modulates thin filament cooperativity. Our hypothesis is that the impact of the N terminus of cTnT on thin filament activation is modulated by a shift from α- to β-MHC isoform. We engineered two recombinant proteins by deleting residues 1–43 and 44–73 in rat cTnT (RcTnT): RcTnT(1–43Δ) and RcTnT(44–73Δ), respectively. Dynamic and steady-state contractile parameters were measured at sarcomere length of 2.3 µm after reconstituting proteins into detergent-skinned muscle fibers from normal (α-MHC) and propylthiouracil-treated (β-MHC) rat hearts. α-MHC attenuated Ca(2+)-activated maximal tension (∼46%) in RcTnT(1–43Δ) fibers. In contrast, β-MHC decreased tension only by 19% in RcTnT(1–43Δ) fibers. Both α- and β-MHC did not affect tension in RcTnT(44–73Δ) fibers. The instantaneous muscle fiber stiffness measurements corroborated the divergent impact of α- and β-MHC on tension in RcTnT(1–43Δ) fibers. pCa(50) (-log of [Ca(2+)](free) required for half-maximal activation) decreased significantly by 0.13 pCa units in α-MHC + RcTnT(1–43Δ) fibers but remained unaltered in β-MHC + RcTnT(1–43Δ) fibers, demonstrating that β-MHC counteracted the attenuating effect of RcTnT(1–43Δ) on myofilament Ca(2+) sensitivity. β-MHC did not alter the sudden stretch–mediated recruitment of new cross-bridges (E(R)) in RcTnT(1–43Δ) fibers, but α-MHC attenuated E(R) by 36% in RcTnT(1–43Δ) fibers. The divergent impact of α- and β-MHC on how the N terminus of cTnT modulates contractile dynamics has implications for heart disease; alterations in cTnT and MHC are known to occur via changes in isoform expression or mutations.